Tawẓīf al-Tiknūlūjiyā al-Ta‘līmiyyah fī Ta‘līm al-I‘rāb: Dirāsah fī Tanmiyat Mahārah al-Qirā’ah ladā Muta‘allimī al-Lughah al-‘Arabiyyah - Raudatussolihah, Baiq; Taufiqi Kholida, Masita; Fathurrahman, Ali (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2026)
This study aims to analyze the utilization of educational technology in teaching i‘rāb at Dar at-Taklim Islamic Junior High School, Tangar, East Lombok, focusing on three main aspects: the forms of technology utilization in i‘rāb instruction, teachers’ strategies in integrating digital media into the learning process, and its contribution to the development of students’ mahārah al-qirā’ah (reading skills). This study employed a qualitative descriptive approach, with data collected through classroom observations, interviews with teachers and students, and analysis of instructional documents. The data were systematically analyzed to identify patterns of technology integration, teachers’ pedagogical strategies, and their influence on students’ understanding of Arabic grammatical structures and reading proficiency.The findings reveal that the use of educational technology, such as Arabic language learning applications, interactive presentations, instructional videos, and online learning resources, creates a more interactive and contextual learning environment. Teachers implemented various strategies, including the visualization of i‘rāb rules, digital-based exercises, and the use of audiovisual media to facilitate students’ comprehension of Arabic grammatical structures. Furthermore, the integration of technology in i‘rāb instruction was found to contribute positively to enhancing student engagement, mastery of Arabic grammar, and the ability to read Arabic texts more accurately while achieving deeper comprehension of the content. This study highlights the importance of developing technology-based i‘rāb instructional models as a pedagogical innovation to improve mahārah al-qirā’ah at the junior secondary level within Islamic educational institutions.